Growth and productivity of coffee irrigated according to different sources of nitrogen - de Lima, Luara Cristina; Gonçalves, Anderson Carvalho; Fernandes, André Luis Teixeira; Silva, Reginaldo De Oliveira; Lana, Regina Maria Quintão (Coffee Science - ISSN 1984-3909, 2016)
Coffee is one of the main agricultural crops and for high production in farming, especially irrigated, large nitrogen (N) contents are used every year, and is fundamental to the study of techniques for the rational use of this element. The objective of this study was to evaluate the vegetative and productive parameters of the coffee according to various sources, doses and forms of application of N in irrigated coffee. The experiment was carried out at the Experimental Field Izidoro Bronzi - ACA, in the city municipality of Araguari, state of Minas Gerais, during the crop 2010/2011, 2011/2012, 2012/2013 and 2013/2014. Fertilizer was applied in treatments with conventional fertilization three split applications (November, January and March all evaluated years) and fertigation, it was used weekly from September of each year, until June of the following year, in doses of 210 and 300 kg ha-1 of N were conducted reviews of biometric aspects, productivity, fruit in 4th and 5th and we of maturation, observing the interference of N fertilization on these aspects were made. The N generates an increase in the production of fertilized treatments compared to control, reaching increases of 151%. Its no possible to establish a coherent relationship with N for other characteristics due to randomness of the data. Agricultural urea to be applied by fertigation demonstrates not be better applied conventionally, but proves to be better than the polymerized urea applied conventionally. The applied ammonium nitrate can be conventionally considered the best source of N when analyzing all the variables together. For fertigation, the use of agricultural urea 300 kg ha-1 increments to provide uniformity in fruit maturation.